2003
DOI: 10.1080/19485565.2003.9989075
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting nutritional status in female adults in Dhaka slums, Bangladesh

Abstract: This study looks at women from the slums in Mohammadpur, Dhaka, Bangladesh, where 54 percent of women's BMI was less than 18.5. Fifty percent of the Dhaka slum population lived below the poverty line. Logistic regression showed that women with income above 1,500 taka per capita were 1.78 times more likely to have a higher BMI (odds ratio 1.7863; CI = 0.671-3.639). Women with their own savings were 1.89 times more likely to have higher BMI (odds ratio 1.879; CI = 0.01163-1.6431). Women were 4.5 times more likel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 10 publications
5
21
0
Order By: Relevance
“…Because of poor people cannot buy expensive nutritious food items like meat, milk, fruits regularly. Several recent studies in Bangladesh [25][26][27][34][35] and worldwide [14,15,36] also found the similar results. Importantly, national income contributed to increase literacy rate, dietary food intake, preserve food, etc.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Because of poor people cannot buy expensive nutritious food items like meat, milk, fruits regularly. Several recent studies in Bangladesh [25][26][27][34][35] and worldwide [14,15,36] also found the similar results. Importantly, national income contributed to increase literacy rate, dietary food intake, preserve food, etc.…”
Section: Discussionsupporting
confidence: 74%
“…Such conditions could be linked to different environmental, behavioral and individual risk factors [13]. The BMI depends on many factors like age, education, occupation, household economic status, food habits and sedentary lifestyles [6,[14][15]. The underweight are susceptible to poor maternal and infant health as well as childhood growth problems and compromised mental development [16].…”
Section: Introductionmentioning
confidence: 99%
“…A large population study conducted in India reported a relatively similar finding where 31.2 % of their women were underweight, with only 9.4 % in overweight and 2.6 % in obese categories [17]. One local study that focused on women living in the slum areas in Bangladesh capital (Dhaka) reported that more than half (54 %) of these women were underweight, and concluded that the most likely contributing factor would be extreme poverty [26]. Among the underweight mothers (BMI ≤ 18.5), most of them had mild CED (grade I), more than one-fourth had moderate CED (grade II), and a relatively high percentage (11.9 %) suffered severe CED (grade III).…”
Section: Discussionmentioning
confidence: 99%
“…Early empirical work had evaluated the extent to which maternal employment was associated with indicators of undernutrition among women (e.g., underweight (body mass index [BMI] <18.5) and children (e.g., underweight [weight-for-age z-score [WAZ] < −2]). Some of these findings reported a decreased risk of undernutrition, while others indicated an increased risk of undernutrition or report null results (Bamji & Thimayamma, 2000;Brown, Yohannes, & Webb, 1994;De Groote, Kennedy, Payongayong, & Haddad, 1994;Engle, 1991Engle, , 1993Engle & Pedersen, 1989;Lamontagne, Engle, & Zeitlin, 1998;Leslie, 1988;Popkin, 1980Popkin, , 1983Pryer, Rogers, & Rahman, 2003;Toyama, Wakai, Nakamura, & Arifin, 2001;Tucker & Sanjur, 1988). Results also suggested heterogeneity in the association by occupation type (e.g., agriculturebased employment) and number of hours worked (Engle, 1991;Engle & Pedersen, 1989;Glick & Sahn, 1998;Leslie, 1988).…”
mentioning
confidence: 99%